2020
DOI: 10.1155/2020/4063201
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metals Nanofiltration Using Nanotube and Electric Field by Molecular Dynamics

Abstract: Heavy metal contamination in the world is increasing the impact on the environment and human life. Currently, carbon nanotubes and boron are some possible ideals for the nanofiltration of heavy metals due to the property of ion selectivity, optimized by the applications of the surface and the application of an external electric field. In this work, molecular dynamic was used to transport water with heavy metals under the force exerted by the electric field action inside nanotubes. This external electric field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 95 publications
0
5
0
Order By: Relevance
“…Functionalized BNNT, similar to functionalized CNT, has a higher adsorption capacity than its pristine type 23 . Azamat et al 24 investigated the ability of CNT and BNNT as membranes to remove Pb ions, Cu, and Hg ions in the presence of an electric field and found that BNNT had a higher adsorption capacity than CNT due to hydrogen bonding with water molecules.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Functionalized BNNT, similar to functionalized CNT, has a higher adsorption capacity than its pristine type 23 . Azamat et al 24 investigated the ability of CNT and BNNT as membranes to remove Pb ions, Cu, and Hg ions in the presence of an electric field and found that BNNT had a higher adsorption capacity than CNT due to hydrogen bonding with water molecules.…”
Section: Introductionmentioning
confidence: 99%
“…Azamat et al 24 investigated the ability of CNT and BNNT as membranes to remove Pb ions, Cu, and Hg ions in the presence of an electric field and found that BNNT had a higher adsorption capacity than CNT due to hydrogen bonding with water molecules. Aroche et al 23 showed that the external electric field affects the performance of CNT and BNNT in the removal of Zn, Cd, Hg, Pb, and Fe ions.…”
Section: Introductionmentioning
confidence: 99%
“…In some situations, it leads to toxic effects such as liver damage and gastrointestinal disturbances. Industrial waste water is the main source of this matter which cause the pollution of rivers and water sources [4]. Several techniques have been employed for removal of heavy metals from aqueous solution including ion exchange [5], ion adsorption on modified natural materials [6], electrodialysis [7,8], chemical precipitation [9], photocatalysis [10], and flocculation processes [3].…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metals are reactive atoms that are toxic to the human body and environment . Copper, mercury, chromium, lead, cadmium, and nickel are the most harmful and are frequently found in higher than the permitted limit in the environment. , Pollution with heavy metals is a problem of great concern due to their non-biodegradability, toxicity, and tendency to be accumulated in living organisms, accompanied by the high volumes of industrial production of wastewaters including heavy metals. , Although heavy metals are naturally present along with other elements in nature, human activities such as industrial production and wastewater have increased the levels of these elements as the pollutants in the water, soil, and atmosphere. Up to now, a number of effective procedures have been prepared for the elimination of heavy metals, such as reverse osmosis, ion exchange, chemical precipitation, electrodialysis, nanofiltration (NF), ultrafiltration, flocculation, coagulation, and floatation. …”
Section: Introductionmentioning
confidence: 99%
“…1 Copper, mercury, chromium, lead, cadmium, and nickel are the most harmful and are frequently found in higher than the permitted limit in the environment. 2,3 Pollution with heavy metals is a problem of great concern due to their non-biodegradability, toxicity, and tendency to be accumulated in living organisms, accompanied by the high volumes of industrial production of wastewaters including heavy metals. 4,5 Although heavy metals are naturally present along with other elements in nature, human activities such as industrial production and wastewater have increased the levels of these elements as the pollutants in the water, soil, and atmosphere.…”
Section: Introductionmentioning
confidence: 99%